Effectiveness of cognitive therapy group training based on mindfulness on reducing dysfunctional attitudes and automatic thoughts of women suffering from postpartum depression - Borna, Arezoo (Psychology of Woman Journal, 2021)
The present study was conducted to determine the effectiveness of mindfulness-based cognitive therapy group training in reducing dysfunctional attitudes and automatic thoughts in women suffering from postpartum depression. The current research method was quasi-experimental with a pre-test-post-test design with a control group. The statistical population of this research is all women referred to Royin Tan Arash Hospital in the period from April to June 2021. Those who obtained a higher score (according to the clinical cut-off point) in this test were selected as a research sample in the size of 20 women and were replaced in two experimental and control groups where the number of each group was ten women. After the ineffective attitude and automatic thoughts questionnaires were administered to both the control and experimental groups, the experimental group members participated in mindfulness training sessions for eight sessions, each lasting 90 minutes. None of the control group members participated in the mindfulness training sessions. The data obtained from the pre-test and post-test were analyzed through analysis of covariance using Spss-23 software. The research results showed that cognitive therapy training based on mindfulness reduced ineffective attitudes (F=30.30, P=0.001) and automatic thoughts (F=34.21, P=0.001) in the experimental group. In general, the findings of this research indicate that cognitive therapy based on mindfulness can be considered an effective intervention in reducing negative automatic thoughts and ineffective attitudes of women suffering from postpartum depression.